2010
DOI: 10.4049/jimmunol.1000484
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation with IL-4Rα Antisense Oligonucleotide Prevents Respiratory Syncytial Virus-Mediated Pulmonary Disease

Abstract: Respiratory syncytial virus (RSV) causes significant morbidity and mortality in infants worldwide. Severe RSV infections in infants cause bronchiolitis, wheeze, and/or cough and significantly increase the risk for developing asthma. RSV pathogenesis is thought to be due to a Th2-type immune response initiated in response to RSV infection, specifically in the infant. Using a neonatal mouse system as an appropriate model for human infants, we sought to determine whether local inhibition of IL-4Rα expression duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
47
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 39 publications
8
47
1
Order By: Relevance
“…In fact, these results were strikingly similar to those that we previously obtained with antisense oligonucleotides to IL-4R␣: the moderate downregulation of IL-4R␣ during neonatal RSV infection completely abolished reinfection-associated airway hyperactivity and significantly decreased Th2-biased responses (6). We believe this phenomenon to be due to fine-tuning of IL-4R␣ signaling, which results in a rebalancing of the immune response so that Th2 cells no longer skew the immune response.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In fact, these results were strikingly similar to those that we previously obtained with antisense oligonucleotides to IL-4R␣: the moderate downregulation of IL-4R␣ during neonatal RSV infection completely abolished reinfection-associated airway hyperactivity and significantly decreased Th2-biased responses (6). We believe this phenomenon to be due to fine-tuning of IL-4R␣ signaling, which results in a rebalancing of the immune response so that Th2 cells no longer skew the immune response.…”
Section: Discussionsupporting
confidence: 88%
“…Although it is difficult to dissociate the antiviral effects of IFN-␣, our previous study clearly demonstrated that enhanced IL-4R␣ expression on neonatal Th cells compared to that on adult Th cells plays a significant role in the development of the Th2-biased immunopathologies following RSV reinfection (4). Furthermore, the reduction of IL-4R␣ on Th2 cells during primary infection prevents Th2 bias, airway hyperreactivity, mucus hyperproduction, and inflammation upon reinfection without affecting the viral load (6). In line with this observation, the data presented here demonstrate that IFN-␣ treatment prior to RSV infection reduces the expression of IL-4R␣ on Th2 cells (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It is, however, clear that these forms of sampling represent the mixture of conventional Th2 contributions (in ours and other studies, ref. 44) with those of a number of other cell types. With respect to CD4 + T cells, for instance, a major source of IL-9 would be the Th9 cell population (45).…”
Section: Discussionmentioning
confidence: 97%